Auditory and Vestibular Characteristics of NLRP3 Inflammasome Related Autoinflammatory Disorders: Monogenic Hearing Loss Can Be Improved by Anti-interleukin-1 Therapy - Nakanishi, Hiroshi; Yamada, Satoshi; Kita, Junya; Shinmura, Daichi; Hosokawa, Kumiko; Sahara, Sosuke; Misawa, Kiyoshi (Frontiers in Neurology, 2022)
Inflammasomes are large multimeric protein complexes which regulate the activation of the proinflammatory cytokines interleukins-1β and−18 and inflammatory cell death called pyroptosis. NLRP1, NLRP3, NLRC4, AIM2, and pyrin can induce the formation of inflammasomes. Of these, the NLRP3 inflammasome is the most well-characterized. Recent studies revealed that variants of the NLRP3 gene cause genetic diseases, including systemic inflammatory syndrome called cryopyrin-associated periodic syndrome (CAPS) and non-syndromic sensorineural hearing loss DFNA34. NLRP3 variants cause CAPS and DFNA34 by constitutively activating the NLRP3 inflammasome and increasing IL-1β release. Patients with CAPS show systemic inflammatory symptoms, and hearing loss is a characteristic feature. Patients with CAPS and DFNA34 show progressive bilateral sensorineural hearing loss. Hearing loss has unique characteristics that can be improved or stabilized by anti-interluekin-1 therapy, although it is usually difficult to alleviate genetic hearing loss by drugs. However, it should be noted that there is a window of opportunity to respond to treatment, and younger patients are most likely to respond. It is important to know the characteristics of CAPS and DFNA34 for early diagnosis, and mutation analysis of NLRP3 will lead to a definite diagnosis. In this review, we summarize the current understanding of the mechanisms of the NLRP3 inflammasome and characteristics of patients with CAPS and DFNA34, especially focused on auditory and vestibular findings.